Primary lung chordoma: a case report - Naoko Shigeta; Tetsuya Isaka; Kyoko Ono; Mio Tanaka; Tomoyuki Yokose; Hiroyuki Adachi; Wataru Usuba; Hiroyuki Ito (BMC, 2024)
Abstract Background Chordoma, a rare malignant tumor arising from notochordal tissue, usually occurs along the spinal axis. Only a few published reports of primary lung chordomas exist. Herein, we present a case of primary lung chordoma and discuss important considerations for diagnosing rare chordomas. Case presentation We report a case of primary lung chordoma in a 39-year-old male with a history of testicular mixed germ-cell tumor of yolk sac and teratoma. Computed tomography revealed slow-growing solid lesions in the left lower lobe. We performed wedge resection for suspected germ-cell tumor lung metastasis. Histologically, large round or oval cells with eosinophilic cytoplasm were surrounded by large cells with granular, lightly eosinophilic cytoplasm. Tumor cells were physaliphorous. Immunohistochemistry was positive for brachyury, S-100 protein, epithelial membrane antigen, vimentin, and cytokeratin AE1/AE3, suggesting pulmonary chordoma. Re-examination of the testicular mixed germ-cell tumor revealed no notochordal elements. Although some areas were positive for brachyury staining, hematoxylin and eosin (HE) staining did not show morphological features typical of chordoma. Complementary fluorescence in situ hybridization (FISH) of the lung tumor confirmed the absence of isochromosome 12p and 12p amplification. Thus, a final diagnosis of primary lung chordoma was established. Conclusions In patients with a history of testicular mixed germ cell tumors, comparison of histomorphology using HE and Brachyury staining of lung and testicular tumors, and analyzing isochromosome 12p and 12p amplification in lung tumors using FISH is pivotal for the diagnosis of rare lung chordomas.